The historiography of formation and development of theoretical electrical engineering in Ukraine (XX – early XXI century) - Lavrinenko, Olga (Instytut Spraw Administracji Publicznej, Polska, 2020)
The article is devoted to the coverage of the level of scientific elaboration of formation and development of theoretical electrical engineering in Ukraine in the 20th – beginning of the 21st centuries. The author has conducted a comprehensive historiographical analysis of the numerous publications on the formation of this direction in Ukraine and has identified two chronological periods: Soviet era (1930–1991) and modern period (after 1991). Each of these periods have its own characteristics that influenced the collection of scientific literature. Therefore, the complex historiographical research has comprehensively highlighted the directions of scientific investigation and formed the hierarchical structure of the scientific historical work, and the gradual analysis of the literature helped to reveal and distribute the information on the formation and development of theoretical electrical engineering as the basic direction of electrical engineering in Ukraine.

Стаття присвячена висвітленню рівня наукової розробленості становлення та розвитку теоретичної електротехніки в Україні у ХХ ст. – на початку ХХ ст. Автором проведено комплексний історіографічний аналіз публікацій стосовно становлення цього напряму в Україні, виокремлено два хронологічні періоди: період радянської доби (1930–1991 рр.) та сучасний період (після 1991 р.). Серед історичних праць радянського періоду виокремлено праці з історії фізики та розвитку теорії електрики і магнетизму, праці, які описують формування електротехнічної освіти в Україні та становлення наукового електротехнічного напряму. Другий період історіографічних досліджень характеризується значним збільшенням публікацій, появою різнопланових праць з історії теоретичної електротехніки, вищої електротехнічної школи, галузевого сектору електротехнічної науки, великою кількістю наукової біографістики. Отже, комплексне історіографічне дослідження всебічно висвітлило напрями наукового пошуку та сформувало ієрархічну структуру наукової історичної роботи, а поступовий аналіз літератури дав змогу розкрити та поширити відомості щодо формування та розвитку теоретичної електротехніки як базового електротехнічного напряму в Україні.
Історіографія становлення та розвитку теоретичної електротехніки в Україні (ХХ ст. – початок ХХІ ст.)
Keywords: historiographical studies; electrical engineering and magnetism; theoretical basics of electrical engineering; scientific schools; scientific biography; Ukraine